Green Life, Green Campus (Kajian Pemahaman Kehidupan Hijau di Lingkungan Akademisi Universitas Islam Negeri Sultan Syarif Kasim Riau) - Sukma Erni (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
Green life now is a necessity. To realize the lives that are already degraded it takes the efforts of all parties, especially the universities as the agents of change and formation of future resources. This study was conducted to look at The Understanding Study In The Green Life Of State Islamic University Academics Of Sultan Syarif Kasim Riau. The Presentation of the data is done simply by the way of sorting out the percentage of knowledge. The results obtained showed that the academic community knowledge of the state Islamic University of Suska Riau is not so good that it takes an ongoing socialization process.